Experience in the organization of the educational process in the medical university during the war in Ukraine - Ivanchenko, O. Z.; Melnikova, O. Z.; Lurie, K. I.; Іванченко, Олена Зенонівна; Мельнікова, Оксана Зенонівна; Лур'є, Костянтин Ігорович (My University, 2022)
The article summarizes the students' learning experience, which was developed by the efforts of the entire staff of the medical university during the war. The high-quality educational activity involves the organization of a continuous educational process under the condition of complete safety of all participants of this process, which can be ensured by using synchronous and asynchronous educational modes. A necessary component of professional training is the acquisition of practical skills and communication skills of students, which was carried out in the project "Summer school for consolidation of practical skills". As part of the cooperation between universities in the implementation of the principle of academic mobility of students, students from other higher education institutions participated in the project.
Keywords: synchronous and asynchronous mode of online learning; practical skills; academic mobility